Investigation of octahedral hole geometry and strain induced of doped perovskite barium titanate (BaTi0.6Ni0.2Fe0.1O3) - Aroon Saelor (2018)
The investigation of structural and electric properties of doped perovskite barium titanate (BaTi0.6Ni0.2Fe0.1O3) was carried out in this study. All possible structures were generated and assessed. The change in octahedral hole geometry and electronic structure were calculated and evaluated using density functional theories (DFT) with LDA/PWC functions. The results indicate the distortion of octahedral hole of iron and its neighboring site. In addition, the direction of strain induced vectors was analyzed and located. © 2014 Taylor & Francis Group, LLC.